Residual grade and waste abaca fibers as reinforcement for packaging and printing/writing papers from recycled fiber - Austria, Erlinda L.; Domingo, Emmanuel P.; Mari, Cesar O.; Torres, Adela S. (2019)
Fiber dimensions of residual grade abaca (tow grade) and waste abaca fibers (tuxy and stripping wastes) were measured. The fibers were found extremely long with thin cell walls. Fiber slenderness or felting point, flexibility, Runkel, and Muhlsteph ratios all indicate suitability for papermaking. Soda-pulping of the fibers, tow, and Tx80Sw20 (i.e., tuxy and stripping waste fibers combined at 80:20) at NaOH charges of 8, 10, and 12%, yielded tow pulp twice greater than Tx80Sw20 pulp. Beating evaluation of tow-grade fiber pulped at 8% NaOH and the corresponding handsheet tests showed that acceptable beating time is 15?30 min. The Tx80Sw20 blend, on the other hand, already had a low freeness of only 227 mL and thus needed no further beating. The pulps were used as reinforcement for the production of papers from recycled or secondary fibers. The 80:20 blends of tow and Tx80Sw20 pulps were used to replace 3?10% levels of old corrugated cartons (OCC) to produce packaging paper, or mixed office wastes (MOW) to produce printing/writing paper. Results of tests on the handsheets produced therefrom indicate significant improvement in strength properties, even at low levels of 3?5% of reinforcement. (Author's abstract)